Perawatan Lengkung Di Km 2+2/400 Lintas Manggarai – Jatinegara - Sholihin, Mohammad; Dwiatmoko, Hermanto; Septanto, Djoko (Politeknik Perkeretaapian Indonesia Madiun, 2020)
Curves number 2 and 18 on Manggarai - Jatinegara cross are part of cross in DAOP (Operation Area) 1 Jakarta area. The reliability of an arch in its role in the operation of the railway is important even be a major factor. Therefore, perfection in care is absolute and a major requirement of a condition where the arch can be said to be reliable. But not all arches have the same elevation value as the calculated result. Thus it required an analysis of the level of care arch the arch reliability. From the results of secondary and primary data analysis then obtained data related to the condition of curve number 2 and 18 cross Manggarai - Jatinegara still not good in terms of changes in arrows and rail elevation. Calculation and analysis of data used dilihiat in terms of curved geometry conditions that is curved radius, transverse arch, rail elevation, ideal curve graph conditions and human resources managers. After analyzing the data and then compared with the existing standard, the implementation of curved treatment has been said to be only just not maximal, it can be suggested that it needs to be maintained treatment of the curve condition continues with the inspection in accordance with the provisions and immediately repaired the curved geometry is lacking, Arch back to normal and do maintenance by using the MTT machine at the time of treatment at night so that the implementation of the treatment is more suitable as expected and also did not happen trial and error.